(untitled) (Scientific journal of the Fergana State University, 2023)
The article reveals the issues of humanistic anthropocentrism of the European Renaissance on the example of the socio-philosophical teaching of Michel Montaigne. Also important for young people are the humanistic essence of the ideas of self-consciousness, faith, purity of conscience in the work of the thinker "Experiments", in-depth study and evaluation of the eternal heritage, the acquisition of modern scientific achievements, responsibility and noble qualities. describes the formation of a spiritual image.